Pengembangan Sistem Informasi (Website & Aplikasi) Desa Sumberbrantas, Kota Batu untuk Peningkatan Kepariwisataan & Kesejahteraan Masyarakat - Muhaimin Achsin; Rita Parmawati; Johan Wahyudi; Zaqlul Iqbal (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
The development of a village information system must be done because it is mandated by Law no. 6 of 2014 concerning villages, especially article 86. In article 86 point (2), it states that "the government and regional governments are obliged to develop a village information system and rural area development," and in point (3), "the village information system as referred to in paragraph (2) includes facilities hardware and software, networks, and human data sources”. Brawijaya University's strategic community service team developed an information system in Sumberbrantas village, Batu City, in the form of websites and applications, as well as capacity building. The methods used are survey, observation, brainstorming, youth involvement, data collection, creating website & application, training, and launching as well as socialization. The purpose of making the Sumberbrantas.id website and application is an information system, service, product marketing place, information delivery, government activities and villagers, as well as supporting the development of tourism in Sumberbrantas village. This community service activities take place in Sumberbrantas from June to October 2022. Keywords: Information system, Sumberbrantas Village, Website & Application